Are Credit Unions Too Small? - Wheelock, David C.; Wilson, Paul W. (The Review of Economics and Statistics, 2011)
U.S. credit unions serve 93 million members, hold 10% of U.S. savings deposits, and make 13.2% of all nonrevolving consumer loans. Since 1985, the share of U.S. depository institution assets held by credit unions has nearly doubled, and the average (inflation-adjusted) size of credit unions has increased over 600%. We use a local-linear estimator, dimesion-reduction techniques, and bootstrap methods to estimate and make inference about ray scale and expansion-path scale economies. We find substantial evidence of increasing returns to scale among credit unions of all sizes, suggesting that further consolidation and growth among credit unions are likely.